Influence of previous COVID-19 exposure and vaccine type (CoronaVac, ChAdOx1 nCov-19 or BNT162b2) on antibody and cytokine (Th1 or Th2) responses - Diana Lourdes Padilla-Bórquez; Mónica Guadalupe Matuz-Flores; Jorge Hernández-Bello; Jesús Alfredo Rosas-Rodríguez; Francisco Javier Turrubiates-Hernández; Samuel García-Arellano; Guillermo González-Estevez; Hazael Ramiro Ceja-Galvez; Edith Oregon-Romero; Alberto López-Reyes; Jose Francisco Muñoz-Valle (Taylor & Francis Group, 2024)
To achieve global herd immunity, widespread vaccination is the most effective strategy. Vaccines stimulate the immune system, generating cytokines and chemokines, isotype antibodies, and neutralizing antibodies; all these molecules collectively provide a more comprehensive characterization of the immune response post-vaccination. We conducted a longitudinal study in northwestern Mexico, involving 120 individuals before vaccination and after the first dose of the SARS-CoV-2 vaccine, and 46 individuals after their second dose. Our findings reveal that antibody levels stabilize over time; cytokine levels generally increase following the first dose but decrease after the second dose and higher than normal levels in IgG1 and IgG3 concentrations are present. Most of the innate cytokines determined in this study were higher after the first dose of the vaccine. Regardless of previous infection history, this finding suggests that the first dose of the vaccine is crucial and may stimulate immunity by enhancing the innate immune response. Conversely, increased levels of IL-4, indicative of a Th2 response, were found in individuals without prior exposure to the virus and in those vaccinated with CoronaVac. These results suggest that the immune response to COVID-19 vaccines is multi-faceted, with preexisting immunity potentiating a more robust innate response. Vaccine type plays a critical role, with genetic vaccines favoring a Th1 response and inactivated vaccines like CoronaVac skewing toward a Th2 profile.